Question

# Graph the equation

Hint:

### To plot the graph of an equation, first we make a table of points satisfying that equation. Then we draw an x-axis and y-axis on the graph. After that we scale both the axis according the values we get in the table. Lastly, we plot the points from the table on the graph and join them to get the required curve.

## The correct answer is: After plotting the points, we join them with a line to get the graph of the equation.

### Step by step solution:

The given equation is

Y = -0.5x

First we make a table of points satisfying the equation.

Putting x = 0 in the above equation, we will get, y = 0

Similarly, putting x = 1, in the above equation, we get y = -0.5

Continuing this way, we have

For x = -1, we get y = 0.5

For x = 2, we get y = -1

For x = -2, we get y = 1

Making a table of all these points, we have

Now, we plot these points on the graph

After plotting the points, we join them with a line to get the graph of the equation.

First we make a table of points satisfying the equation.

Putting x = 0 in the above equation, we will get, y = 0

Similarly, putting x = 1, in the above equation, we get y = -0.5

Continuing this way, we have

Making a table of all these points, we have

Now, we plot these points on the graph

After plotting the points, we join them with a line to get the graph of the equation.

We can find the tabular values for any points of x and then plot them on the graph. But we usually choose values for which calculating y is easier. This makes plotting the graph simpler. We can also find the values by putting different values of y in the equation to get different values for x. Either way, we need points satisfying the equation to plot its graph.

### Related Questions to study

### The constant term in the product (𝑥 + 3) (𝑥 + 4) is

### The constant term in the product (𝑥 + 3) (𝑥 + 4) is

### Write the product in standard form. (3𝑦 − 5)(3𝑦 + 5)

This question can be easily solved by using the formula

(a + b)(a - b) = a2 - b2

### Write the product in standard form. (3𝑦 − 5)(3𝑦 + 5)

This question can be easily solved by using the formula

(a + b)(a - b) = a2 - b2

### Write the product in standard form. (𝑥 − 4)(𝑥 + 4)

This question can be easily solved by using the formula

(a + b)(a - b) = a2 - b2

### Write the product in standard form. (𝑥 − 4)(𝑥 + 4)

This question can be easily solved by using the formula

(a + b)(a - b) = a2 - b2

### The area of the rectangle is 𝑥^{2} + 11𝑥 + 28. Its length is x + __ and its width is __+ 4. Find the missing terms in the length and the width.

### The area of the rectangle is 𝑥^{2} + 11𝑥 + 28. Its length is x + __ and its width is __+ 4. Find the missing terms in the length and the width.

### Simplify: 12 - [13a - 4(5a -7) - 8 {2a -(20a - 3a)}]

### Simplify: 12 - [13a - 4(5a -7) - 8 {2a -(20a - 3a)}]

### Write the product in standard form. (2𝑥 + 5)^{2}

This question can be easily solved by using the formula

(a + b)2 = a2 + 2ab + b2

### Write the product in standard form. (2𝑥 + 5)^{2}

This question can be easily solved by using the formula

(a + b)2 = a2 + 2ab + b2

### Write the product in standard form. (𝑥 − 7)^{2}

This question can be easily solved by using the formula

(a - b)2 = a2 - 2ab + b2

### Write the product in standard form. (𝑥 − 7)^{2}

This question can be easily solved by using the formula

(a - b)2 = a2 - 2ab + b2

### (𝑥 + 9)(𝑥 + 9) =

This question can be easily solved by using the formula

(a + b)2 = a2 + 2ab + b2

### (𝑥 + 9)(𝑥 + 9) =

This question can be easily solved by using the formula

(a + b)2 = a2 + 2ab + b2

### Find the area of the rectangle.

### Find the area of the rectangle.

### The table below shows the distance a train traveled over time. How can you determine the equation that represents this relationships.

### The table below shows the distance a train traveled over time. How can you determine the equation that represents this relationships.

### Simplify: 4x^{2}(7x -5) -6x^{2}(2 -4x)+ 18x^{3}

### Simplify: 4x^{2}(7x -5) -6x^{2}(2 -4x)+ 18x^{3}

### (𝑎 + (−3))^{2} =

This question can be easily solved by using the formula

(a - b)2 = a2 - 2ab + b2

### (𝑎 + (−3))^{2} =

This question can be easily solved by using the formula

(a - b)2 = a2 - 2ab + b2

### Use the table method to multiply a binomial with a trinomial.

(−3𝑥^{2} + 1) (2𝑥^{2} + 3𝑥 − 4)

### Use the table method to multiply a binomial with a trinomial.

(−3𝑥^{2} + 1) (2𝑥^{2} + 3𝑥 − 4)

### (𝑥 − 2)^{2} =

This question can be easily solved by using the formula

(a - b)2 = a2 - 2ab + b2

### (𝑥 − 2)^{2} =

This question can be easily solved by using the formula

(a - b)2 = a2 - 2ab + b2